THE IMPACf OF BRAND IMAGE AND BRAND AWARENESS ON REPURCHASE INTENTION VIA PERCEIVED QUALITY - Siboro, Mindo Yumanda; Soesanto, Harry Seesaato (Diponegoro Journal of Management, 2015)
Nowadays.  Tourism,  one  of  the Indonesia  commodities  has  been giving  huge    role  in raising  the Indonesia  GDP.  The number of the tourism  in Indonesia  is increasing significantly. Whereas, the number of the local visitors who came to Lake Toba (one of the biggestlourism place in Indonesia)  increasing  slowly.  The aim  of  this  research  is to  examine  the factors   that  may influence tourist to visit Lake Toba. The study surveyed  185 visitors who came to Lake  Toba. The survey period  was from  third week of July  2015 to fourth  week of July 2015.  The data analyses were conducted by confirmatory factor  analysis and structural  equation modeling.  The results of the statistical analysis reflected  that most of the visitors of Lake   Toba are highly  concern about Brand Image four  times more than Brand Awareness.  This study demonstrates  that brand image and   brand  awareness positively  affects perceived  quality.  moreover, perceived  quality    is the factors  that influence the tourist to visit Lake  Toba.